Relación entre depresión y rasgos de personalidad en jóvenes y adultos con conducta intencional suicida de Ibagué, Colombia. - Ovalle-Peña, Oscar; Alejo-Riveros, Argemiro; Tarquino-Bulla, Leidy Carolina; Prado-Guzmán, Katherine (Revista Facultad de Medicina de la Universidad Nacional de Colombia, 2017)
Introduction: Intentional suicidal behavior is one of the most troubling and dangerous medical conditions in the world. It is presumed that for each self-inflicted death, about 20 suicide attempts occur. Objective: To identify the correlation between depression and personality traits in patients who have attempted suicide. Materials and methods: Cross-sectional correlational study involving 25 people aged between 18 and 40 who attempted suicide during 2014 and 2015 in Ibagué, Colombia. A sociodemographic data sheet, the "Big Five" questionnaire and the State-Trait Depression Inventory were used for the analysis. Results: Significant negative correlations are evident in the analyzed sample regarding the personality sub-dimension, the control of emotions and depression as a state, on the one hand, and between the same sub-dimension and dysthymia as a state, on the other. This suggests a lower emotional stability in the presence of depression as a state or as a trait. Other correlations identified refer to a moderate relation between the personality dimension, emotional stability and depression. Conclusion: The variables considered in this study (depression and emotional stability) are of great importance when designing preventive health actions.